Decision Support System in Determining the Level of Success of Teaching Teachers Using the AHP Method - Abdillah, Mhd Khoiri; Hartama, Dedy; Nasution, Rizki Alfadillah (Yayasan Literasi Sains Indonesia, 2023)
This study aims to implement a Decision Support System (SPK) that uses the Analytic Hierarchy Process (AHP) method in assessing and determining the level of success of teachers teaching at SMA Taman Siswa, Bah Jambi Branch. This study uses five assessment criteria, namely the number of attendance, lesson plans, teaching period, learning media, and discipline, as a basis for evaluating teacher performance. In this study, the AHP method was used to calculate the relative weight of each criterion and sub-criteria involved in assessing teacher performance. The data collected from various teachers was evaluated using the AHP method, and the results provide an overview of the level of success of each teacher in carrying out the teaching and learning process. The results showed that among the many existing teachers, Siti Palastri managed to score 0.81002, indicating good performance in the teaching and learning process. The application of this system is expected to assist schools in making decisions regarding teacher performance evaluation in a more objective and structured manner. In addition, this system can provide guidance and recommendations that are more effective in identifying areas for improvement by teachers who have not achieved the expected level of success. Thus, improving the quality of teaching can be achieved through corrective measures that are right on target.